Relationship between Self-efficacy and Quality of Life in Ostomates - F Rafii; Naseh L; Yadegary MA (Iran University of Medical Sciences, 2012)
Background and Aims: Physical, psychological and social problem along with significant changes in life style, diminish stoma patients quality of life. At the meanwhile self-efficacy can improve these patients' quality of life. The aim of this study was to assess the relationship between self-efficacy and quality of life in Ostomates.   Materials and Methods: In this descriptive cross-sectional study, 84 Ostomates who referred to selected educational centers of Tehran University of Medical Sciences and Iranian Ostomy Society (IOS) were recruited by census. The data were collected with City of Hope Quality of Life-Ostomy Questionnaire ( COH-QOL) and Stoma Self-efficacy Scale (Stoma SE Scale) and then analyzed using independent t-test, analysis of variance and regression analysis by SPSS-PC (v. 15).   Results: The half of patients, achieved 50-75% of overall self-efficacy score (84-112). The mean score of stoma care-self-efficacy (55.8 ± 11.6) was more than the mean score of social-self-efficacy (42.1 ± 13.2). Moreover, most of patients were scored 7(of 10) and above for overall quality of life and its dimensions. The mean range of quality of life scores in different domains varied from 6 ± 2 for social dimension to 7 ± 1.5 for physical dimension. a significant positive association were found between self-efficacy and physical (P=0.00, r=0.485) psychological (P=0 . 00, r=0.655), social (P=0.000, r=0.694) and spiritual (P=0.00, r=0.393) dimensions and also with overall quality of life (P=0.00, r=0.687). Also the highest correlation was found between quality of life and social self-efficacy subscale (β=0.695, P=0.000).   Conclusion: With regard to the significant correlation between self-efficacy and different dimensions of Ostomates' quality of life in this study, it is suggested that nurses design and execute appropriate interventions to promote these patients' self-efficacy, especially in social dimension which had the highest association with their quality of life and in this way help to improve these patients' quality of life.